Effect of Leverage, Fiscal Distress, and Fiscal Capacity on COVID-19 Accrual Manipulation - Neni Yusmita; Sandrayati Sandrayati; Okky Savira; Sopiyan AR (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the effects of leverage, fiscal distress, and fiscal capacity on accrual manipulation in provincial governments in Indonesia during 2020–2022. Methodology/approach: The research data used regional government financial reports audited by the Badan Pemeriksa Keuangan (BPK), with a sample size of 102 observations from 34 provinces over three years. The analysis method used was panel data regression with a Random Effects Model (REM) approach. Results: The results show that leverage has no significant effect on accrual manipulation. Conversely, fiscal distress and fiscal capacity have a positive effect on accrual manipulation, indicating that high fiscal pressure and capacity encourage accounting flexibility to maintain the image and meet performance targets. Simultaneously, leverage, fiscal distress, and fiscal capacity contribute to the level of accrual manipulation by local governments during the COVID-19 pandemic. Conclusions: This study concludes that fiscal distress and fiscal capacity significantly influence accrual manipulation among Indonesian provincial governments during the COVID-19 pandemic, whereas leverage has no effect. High fiscal pressure and capacity encourage accounting discretion to maintain the performance. Strengthening fiscal governance and audit oversight is essential for reducing the risk of manipulation in public financial reporting. Limitations: The limitations of alternative indicators and objects to districts/cities. Contributions: These findings have important implications for local governments in strengthening financial governance, auditors in increasing oversight of accrual items vulnerable to manipulation, and future researchers in expanding the variables and scope of research.